The Three Dukes, 1940-1941 (1940)
The Three Dukes, a student musical group at Cal Poly. Left to right: Stanley Raymond, Jim Pappas, and Kenny Hawkins (also went by Ken Hawkins). They were members of the Collegiate Club orchestra. Pappas and Hawkins are playing guitars and Raymond is playing a ukulele.